Legal-Judicial Study of Compulsory Licenses for Exploitation of Invention Right - Ã˜Â¨Ã˜Â®Ã˜ÂªÃ›ÂŒÃ˜Â§Ã˜Â±Ã™ÂˆÃ™Â†Ã˜Â¯, Ã™Â…Ã˜ÂµÃ˜Â·Ã™ÂÃ›ÂŒ (Ã™ÂÃ™Â‚Ã™Â‡ Ã™Âˆ Ã˜Â§Ã˜ÂµÃ™ÂˆÃ™Â„)
The compulsory license for invention right is a working procedure for maintaining interaction between the exclusive rights of the owner and the peopleâs public rights in enjoying social welfare that is foreseen in the international documents and internal rights of many countries. This article is intended to study the definition, instances of issuance, and the rulings for this type of license. In the Iranian law, the compulsory licenses of invention right can be justified by the jurisdiction of the Islamic state, as the grantor of invention right, in determining its limits. Non-exploitation of the invention needed for public use can, under certain circumstances, be regarded as hoarding. Actions resulting in the issuance of this license are, in many instances, an evidence of misusing the right and causes inflicting loss on the society, the prevention of which can be justified by the principle of no harm (lÄ á¸arar).